2019
DOI: 10.1038/s41598-019-50854-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of recombinant Par j 1 and Par j 2 resembling the allergenic epitopes of Parietaria judaica pollen

Abstract: The weed wall pellitory, Parietaria judaica, is one the most important pollen allergen sources in the Mediterranean area causing severe symptoms of hay fever and asthma in allergic patients. We report the expression of the major Parietaria allergens, Par j 1 and Par j 2 which belong to the family of lipid transfer proteins, in insect cells. According to circular dichroism analysis and gel filtration, the purified allergens represented folded and monomeric proteins. Insect cell-expressed, folded Par j 2 exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In Middle and Southern Europe and America grass pollen allergy dominates ( 88 ) and can be approached with BM32. In the Mediterranean area olive pollen and certain weeds such Parietaria are common requiring hyposensitization with Ole e 1 and Par j 1 as well as Par j 2 ( 89 , 90 ), respectively. In Eastern Europe and parts of the USA ragweed dominates and mugwort pollen is important in Central Asia ( 91 , 92 ).…”
Section: Unique Features Of Recombinant B Cell Epitope-based Peptide mentioning
confidence: 99%
“…In Middle and Southern Europe and America grass pollen allergy dominates ( 88 ) and can be approached with BM32. In the Mediterranean area olive pollen and certain weeds such Parietaria are common requiring hyposensitization with Ole e 1 and Par j 1 as well as Par j 2 ( 89 , 90 ), respectively. In Eastern Europe and parts of the USA ragweed dominates and mugwort pollen is important in Central Asia ( 91 , 92 ).…”
Section: Unique Features Of Recombinant B Cell Epitope-based Peptide mentioning
confidence: 99%
“…For this purpose, recombinant Amb a 6 was produced in a eukaryotic expression system, i.e., in insect cells. Eukaryotic expression in insect cells was chosen because previous studies have found for the nsLTP from Parietaria judaica pollen, i.e., Par j 2, that the insect cell-expressed allergen exhibited a higher IgE reactivity and allergenic activity [ 42 ]. Highly pure and folded rAmb a 6 was obtained exhibiting the expected molecular mass according to its amino acid sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were pre-incubated overnight with patient serum heat-inactivated at 55 °C for 25 min [ 57 ] diluted 1:10 in MEM supplemented with 10% heat-inactivated fetal bovine serum (HI FBS), 100 U/mL penicillin–streptomycin, 0.2 mM L-glutamine, 0.2 mg/mL hygromycin B, and 0.2 mg/mL geneticin (Thermo Fisher Scientific). Six different allergen concentrations (1000, 100, 10, 1, 0.1, and 0.01 ng/mL) from rAmb a 6; Par j 2, kindly provided by Prof. Rudolf Valenta [ 42 ]; and natural Amb a 1.01 (nAmb a 1.01) as a benchmark kindly provided by Dr. Frank Stolz were used to test allergenic activity. The assay was performed with minor modifications from the previously described assay [ 58 ], namely exposure to the allergen for 1 h at 37 °C, 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…93,[239][240][241] For instance, basophil activation induced by mix of increasing concentrations of the four major timothy grass pollen allergens (rPhl p 1, 2, 5, and 6) was reduced during recombinant B cell epitope-based vaccine (BM32) immunotherapy of patients with grass pollen allergy. 240 Furthermore, rPhl p 5 dependent basophil activation inhibition with SCIT sera demonstrated that immunotherapy-induced allergen-specific IgG antibodies are not long-lasting after treatment discontinuation. 242 In weed pollen allergy, Parietaria judaica represents one of the main sources of allergens in the Mediterranean area with Par j 1 and Par j 2 as major allergens.…”
Section: Grass and Weed Pollen Allergensmentioning
confidence: 99%
“…221 BAT is important for the characterization of novel recombinant, hypoallergenic, peptide-based vaccines for grass pollen allergy and has become a major tool for evaluating change in allergenicity when basophils from patients allergic to grass pollen are tested with novel vaccines peptides and/or carriers. 93,[239][240][241] For instance, basophil activation induced by mix of increasing concentrations of the four major timothy grass pollen allergens (rPhl p 1, 2, 5, and 6) was reduced during recombinant B cell epitope-based vaccine (BM32) immunotherapy of patients with grass pollen allergy. 240 Furthermore, rPhl p 5 dependent basophil activation inhibition with SCIT sera demonstrated that immunotherapy-induced allergen-specific IgG antibodies are not long-lasting after treatment discontinuation.…”
Section: Grass and Weed Pollen Allergensmentioning
confidence: 99%